Assess the design of lorries and quarries for aggregates transport. Report to the Minerals Industry research Organisation - Brighton, James L.; Richards, Terence E. (Cranfield University, 2010)
The majority of aggregates extracted in the UK are transported from the quarry to the point of sale by construction trucks of either rigid chassis or articulated vehicle design. These vehicles have a unique set of requirements for haulage logistics as many of them must be capable of driving on unmade surfaces and constructed dirt roads not only within the quarry but more importantly at the goods destination. Such vehicles have to balance the on-road requirements of minimum energy consumption, low capital cost, low maintenance and low noise with the off road requirements of maintaining overall mobility whilst minimising their impact on the environment. This project investigates the environmental impacts of these vehicles and evaluates their design and use from an environmental perspective to establish whether changes to vehicle design or the layout of the quarries could lessen the impacts. The project considered current practices used for aggregate transport by road including operational methods vehicle choice and logistics. A structured survey technique was used to gather data from quarries producing sand and gravel, limestone and igneous metamorphic rock, located throughout the UK. The predominant findings were: 85% of road going aggregate transport trucks were required to travel on unsealed surfaces within the quarry. Trucks may be required to travel on unsealed surfaces at the point of delivery. 7% of the quarries surveyed had no means of cleaning debris from trucks before they left the quarry. All quarries covered loads when travelling on the highway.The major environmental impacts were: Aggregate transport trucks generate a significant amount of noise especially when unladen. Aggregate transport trucks can contaminate the public highway, with quarry and/or delivery point acquired debris, both near to, and at some distance from the quarry depending on prevailing weather conditions. To corroborate these findings using the general public's perspective, a small public survey was conducted using a face to face structured interview technique in three villages near to quarry operations. The results of this survey confirmed that noise from unladen trucks and debris deposited on the highway were the most significant impacts. To further investigate these issues an experiment was conducted to determine how the noise level from construction trucks compared to other road vehicles on the public highway. The results highlight the potential for empty trucks to generate significantly high impulse noise when travelling over uneven surfaces including potholes, manhole covers and drains. The predominant source of this noise is from the relative movement between the body and chassis. To control this movement the design of body damping systems should be investigated as a low cost solution. The major source of material transfer into the environment was via the trucks tyres. Experimental results showed that halving the tyre's recommended inflation pressure had a significant effect on the material collected within the tyre tread on a sandy loam soil. However, the relationship between soil-tyre adhesion, axle load and the soil's initial bulk density remains unclear and requires a further detailed investigation. A chassis sheeting/enclosure system has been suggested as a low cost method of preventing material being transferred to the chassis which would otherwise fall off on the road. Considering the design of construction trucks three areas were investigated namely; the tyre choice and use, the drive train and the body design along with the vehicles use within the quarry. Tyre choice is predominantly dictated by the aggregate's destination, which is often off-road and hence an off road biased tyre is chosen. Although in reality the majority of sites will not challenge the vehicles mobility, for those that might, the risk of getting a vehicle stuck was too great to justify the use of a more road biased tyre. However, the results from a tread cleaning experiment showed that inflation pressure could be used to reduce tread clogging. It is well reported in the literature that manipulating inflation pressure can improve the tractive capability of a tyre and maintaining the correct road inflation pressure can contribute to reduced fuel consumption. Central tyre inflation systems that are commercially available, allow inflation pressure to be controlled and monitored, however, further research is required to determine the optimum tyre pressure to be used for a given set of operating conditions. Alternative methods of powering truck ancillary equipment, including load bed tipping, have been investigated to reduce the need to run the engine at high speed under low load when tipping the body. A kinetic energy recovery system has the potential to reduce the overall environmental impact of the transport operation by reducing fuel use and engine emissions, and this could be employed to power auxiliary systems, but would be far better utilised to assist with vehicle propulsion during the drive cycle. Considering quarry design three options were highlighted that reduce the environmental impact of road going trucks: 1. Upgrade roads within quarries to enable low rolling resistance on-road tyres to be used on road going trucks without sacrificing mobility. 2. Adopt a demountable body system 3. Employ a flexible conveyor system from excavation face to quarry exitEach option reduces the distance a truck must move within the quarry on un-sealed surfaces. The use of a demountable system would permit a clear segregation between on-road and off road vehicle use within the quarry, but the practical issues associated with the system such as reduced payload and container storage would prevent its widespread adoption where off road capability remains a requirement at the delivery point. The ultimate solution could be considered to be a flexible conveyor system, and low carbon goods transit thereafter. This could be achieved by an advance in conveyor design to allow it to follow the excavator's movements, and transfer the material to the edge of the quarry for onward movement by low carbon transport.